Role of EBUS-TBNA in Mediastinal Staging of NSCLC Patients - Gala, Kunal B.; Shetty, Nitin S.; Rao, Saketh; Pramesh, C.S.; Jiwnani, Sabita; Kumar, Virendra; Tandon, Sandeep; Bhasker, Maheema; Khushal, Rajiv; Kulkarni, Suyash (Journal of Clinical Interventional Radiology ISVIR, 2024)
Purpose Mediastinal staging in non-small-cell lung carcinoma (NSCLC) is essential for appropriate treatment. Invasive mediastinal staging is necessary and mediastinoscopy has been the gold standard, but it is associated with morbidity. The aim of this study is to evaluate the efficacy of endobronchial ultrasonography transbronchial needle aspiration (EBUS-TBNA), compare it with mediastinoscopy, and assess the endosonographic features of lymph nodes for prediction of metastasis.Methods This is a retrospective study of 200 patients with NSCLC who underwent EBUS-TBNA from January 2017 to December 2019. The patients with potentially resectable NSCLC who underwent EBUS-TBNA were included. Standard definitions of sensitivity, specificity, negative predictive value (NPV), positive predictive value (PPV), and diagnostic accuracy were used to determine the diagnostic performance of EBUS-TBNA.Results A total of 200 patients and 616 nodes were studied, out of which 515 were benign and 101 were malignant. Out of 200 cases, 129 (64.5%) had <N2 disease, 59 (29.5%) had N2 disease, and 12 (6%) had N3 disease. EBUS-TBNA had a sensitivity of 78.87%, specificity of 96.12%, NPV of 89.2%, PPV of 91.8%, and accuracy of 90%. Ultrasonography (USG) features of 297 nodes were available and statistical significance was seen in rounded shape, size greater than 10 mm, ill-defined nodal margins, absence of hilum, and hypoechoic echotexture (p < 0.05).Conclusion EBUS-TBNA is a safe and efficacious procedure for mediastinal sampling of NSCLC patients. Familiarity with endosonographic features of lymph nodes, which can predict malignancy in nodes, may further improve the yield of EBUS-TBNA and reduce under-staging.
Keywords: endobronchial ultrasound; FNA; non-small-cell lung cancer